2015
DOI: 10.17576/jsm-2015-4405-13
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Candidaemia in a Malaysian Tertiary Hospital

Abstract: Candidaemia carries high morbidity and mortality, but its conventional diagnosis is

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…This review found only 8 out of 22 studies performed antifungal susceptibility tests. [ 21 22 23 24 25 26 27 28 ] The analysis of these studies shows the increasing resistance of NAC, especially against fluconazole and itraconazole. These results followed previous studies conducted in different parts of the world.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This review found only 8 out of 22 studies performed antifungal susceptibility tests. [ 21 22 23 24 25 26 27 28 ] The analysis of these studies shows the increasing resistance of NAC, especially against fluconazole and itraconazole. These results followed previous studies conducted in different parts of the world.…”
Section: Discussionmentioning
confidence: 99%
“…The studies included are referenced in the list of references. [ 19 20 21 22 23 24 25 26 27 28 32 41 42 43 44 45 46 47 48 49 50 51 ]…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some of the reports deemed relevant in the ELS (16) reported W. anomalus / C. pelliculosa among fungi (mainly Candida spp.) isolated from patients with various serious underlying diseases and suffering infections by opportunistic microbes (Kuiper et al., ; Oliveira et al., ; Taj‐Aldeen et al., ; Lin et al., ; Nidhi et al., ; Tzar et al., ). Additionally, W. anomalus was always a minor fraction (less than 10%) of the isolates.…”
Section: Assessmentmentioning
confidence: 99%